ANALISIS SKRIPSI MAHASISWA PRODI TEKNOLOGI PENDIDIKAN FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI MAKASSAR - Irnayanti; Nurhikmah H; Farida Febriati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The problem in this research is how is the distribution of student thesis research trends and what factors influence the tendency of student thesis research in the Educational Technology Study Program, Faculty of Education, Makassar State University during the last 6 years? The aim is to analyze and describe the distribution of student thesis research tendencies and find out the factors that influence them. The research approach used in this study is a qualitative approach, this type of research is descriptive (descriptive) and uses the case study method. This research was conducted in the library of the Educational Technology Study Program, Faculty of Education, Makassar State University. Collecting data using observation, documentation and interview techniques. The data analysis technique uses the Miles and Huberman model, which consists of data reduction, data presentation, and decision making/verification stages. The results of the study show that over the last 6 years, there has been a change in the focus and scope of thesis research for students of the Educational Technology Study Program, Faculty of Education, Makassar State University. Recently, they are more inclined to use research and development/R&D as much as 46.67%. In addition, the education level chosen as the research location began to be dominated by the Educational Technology Study Program itself. There are 3 factors that influence the tendency of student thesis research in Educational Technology Study Program, Faculty of Education, Makassar State University, namely, student competence, the influence of friends, and the influence of supervisors